High Power 170 GHz Frequency Doubler Based on GaAs Schottky Diodes. Issue 3 (1st May 2022) - TIAN, Yaoling; HE, Yue; HUANG, Kun; JIANG, Jun; LIN, Changxing; ZHANG, Jian
Abstract : The research on high power 170 GHz frequency doubler based on the GaAs Schottky diodes is proposed in this paper. This basic doubler cell is developed with a 50‐μ m‐thick, 600‐μ m‐wide, and 2‐mm‐long AlN substrate with high thermal conductivity to reduce the thermal effect. Besides, power combined frequency doubler has been fabricated to improve the power capacity by a factor of two. Great agreement has been achieved between the simulated results based on electro‐thermal model and measured performances. At room temperature, the 3 dB bandwidth of the single doubler based on GaAs Schottky diodes is 11.8% over the frequency range from 160 to 180 GHz with pumping power of 150 to 330 mW. And the peak efficiency of the doubler is measured to be 33.1%, while the maximum output power is 101.7 mW at 174.08 GHz. As for power combined circuit, the best efficiency is 30.1% with a related output power of 204.6 mW. The proposed methods of developing high power multipliers can be applied in higher frequency band in the future.